Measuring the reliability of SDG 7: the reasons, timing, and fairness of outage distribution for household electricity access solutions. (1st May 2022) - Ferrall, Isa; Callaway, Duncan; Kammen, Daniel M
Abstract: The United Nations identifies ensuring 'access to affordable, reliable, sustainable and modern energy for all' as one of its Sustainable Development Goals for 2030. This article focuses on the comparatively under-investigated question of reliability within the broader goal. We empirically study experienced household electricity reliability using common frameworks in key countries such as Tanzania, Kenya, and India. Datasets represent a diverse set of technologies including solar home systems (SHS), solar pico-grids, and national electricity grids. First, the prevailing reliability metrics—SAIDI and SAIFI—are measured for all datasets. Informed by critical assessments, this article then proposes a suite of new metrics that facilitate improved reliability comparisons by considering the reasons, timing, and fairness of outage distribution. Analyses using our proposed metrics reveal key policy implications for addressing energy poverty in the Global South. Acknowledging that the systems studied provide different capacity, affordability, and carbon footprints, we find that on average, SHS provided comparable hours of lighting to local grid connections, however SHS outages were less equally distributed than those from other sources. In addition, calculations of grid reliability were highly sensitive to measurement techniques and assumptions used, necessitating high resolution data for policy decisions. Finally, economically driven outages conspicuous in pre-paid SHS systems (i.e., disconnections for non-payment) composed a significant portion of experienced unreliability. These findings quantify the important contribution of demand-side affordability to experienced household reliability, thereby allowing for a comprehensive understanding of the reliability of SDG 7.